Caffeine Ingestion With or Without Low-Dose Carbohydrate Improves Exercise Tolerance in Sedentary Adults - Kumar, Namrita; Warren, Gordon L.; Snow, Teresa K.; Millard-Stafford, Melinda (Frontiers in Nutrition, 2019)
Caffeine (CAF) and carbohydrate (CHO) ingestion delay fatigue during prolonged exercise; however, this is primarily documented in endurance trained (ET) athletes. Our purpose was to determine if these ergogenic aids are also effective to improve exercise tolerance in age-matched sedentary (SED) adults. Using a double-blind crossover design, ET and SED (n=12 each group) completed four exercise trials consisting of 30 min cycling at standardized matched work rates 10% below lactate threshold (MOD-EX) followed by a time to fatigue (TTF) ride at individually prescribed intensity of 5% above lactate threshold. After standardized breakfast, the following drink treatments were given before and throughout exercise: CAF (3 mg/kg of body mass, equivalent to 1.5 cups premium brewed coffee), low calorie CHO (LCHO) (0.4% solution, 2 g total CHO), CAF+LCHO, and artificially-sweetened placebo (PLA). SED and ET had similar perceived exertion (RPE) during MOD-EX and TTF (23.8 ± 3.1 and 24.1 ± 2.6 min in ET, SED, respectively). LCHO did not benefit exercise tolerance compared to PLA and was less effective (p<0.05) compared to CAF+LCHO for all participants combined. Thus, the two CAF treatments were averaged, resulting in ~5% lower RPE (p <0.05) and 21% longer TTF (26.3 ± 10.4 min) compared to the no-CAF (21.7 ± 9.9 min) treatments. Blood glucose and lactate were higher (p < 0.05) with CAF vs. no-CAF. SED and ET only differed in metabolic oxidation rates during exercise (higher overall fat oxidation with ET compared to SED). CAF reduces the perceived effort during exercise and increases the capacity for sedentary individuals, as well as trained athletes, to tolerate higher intensity exercise for greater duration; and, these benefits were not further enhanced by ingesting doses of low carbohydrate regularly during exercise.